English level of communicative competence reached by the students of the Department of Journalism of the University of El Salvador at the end of the Intensive English III course in the semester I-2018 = Nivel de competencia comunicativa en inglés alcanzado por los estudiantes del Departamento de Periodismo de la Universidad de El Salvador en el curso de Inglés Intensivo III en el ciclo I-2018. - Posada Martínez, Mayra Alejandra; Rivas Ramos, Héctor José; Valladares, José Bladimir (2024)
The aim of this study was to find out which the English level of Communicative Competence was reached by the students of the Department of Journalism of the University of El Salvador after having taken three Intensive English courses in the Semester I-2018. Since there is not a record of a test or evaluation that demonstrates how developed the English communicative competence of the students is. For that reason, the researchers decided to handle different instruments to measure the level of communicative competence. The instruments that were used were questionnaires, check list and interview. In order to gather the information, the research was focused to three main aspects: The psychosocial profile of students, the professional profile of the teachers, the influence of the resources and teacher-learner materials. All of these factor influence in the development of the students, through the observation the authors could see the behavior of the students, the methodology and techniques that the teachers use to develop the class. Based on this observation, some instruments were designed to be used at the end of the course to measure the development of the English Communicative Competence. The results showed that the average level that students reached was A1+ that means that students are able to use simple instructions but still make basic mistakes, are able to make themselves understood with some pauses. However, the results also showed that many students felt that they were not good enough to establish a conversation with another person and for that reason they refused to be interviewed. For those students that did not want to do the survey said that it was because they felt shy and uncomfortable to have a conversation. For that reason, they only agreed to take the questionnaire.